Study of Seaweed Kappaphycus alvarezii Explants Growth in the Different Salinity Concentrations - Muhammad Aris; Fatma Muchdar; Rusmawati Labenua (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight • The best salinity for the thallus growth of K. alvarezii is 32 mg/L • The salinity indicates the osmotic balance of K. alvarezii seaweed • This osmoregulation process affects the nutrient absorption of K. alvarezii seaweed • This study aims to develop the availibility of superior seeds of K. alvarezii